Haptic Desktop: The Virtual Assistant Designer - Portillo-Rodriguez, O.; Avizzano, C.A.; Chavez-Aguilar, A.; Raspolli, M.; Marcheschi, S.; Bergamasco, M. (2006 2nd IEEE/ASME International Conference on Mechatronics and Embedded Systems and Applications, 2006)
The present paper describes the conceptual and technical design of a new multimodal device named Haptic Desktop System (HDS), which can assist the user in designing/sketching tasks and act as a virtual guide through its force feedback capabilities. The Haptic Desktop System fully integrates proprioceptive, visual, audio and haptic functionalities, into a desk minimizing the visual interference of the physical components. In the proposed approach classic input devices (i.e. keyboard and mouse) have been replaced by new features integrated within audio and haptic. Such features allow commanding and rendering natural force stimuli in a manner, which is completely coherent and co-located with respect to the visual information. The new features of the HDS are designed to reduce considerably the mental load from users during interaction operations